APLIKASI INTEGRASI INTERKONEKSI KEILMUAN DI LEMBAGA PENDIDIKAN TINGGI - Eka Saftri; Ihsan Sa’dudin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2019)
This paper reveals that the unification between various kinds of science is very important for scientific development itself. The union between the science of religion and science is a new breakthrough for existing science. However, the application is still lacking in a more productive domain. UIN Sunan Kalijaga Yogyakarta is a pioneer of Educational Institutions that implement integration and interconnection in their environment. There are various kinds that can be seen, namely the curriculum, teaching staff and even the building. The existence of openness between one knowledge and another makes it a continuous flow of knowledge and influence between one another. Therefore, applying scientific integration and interconnection needs to be applied in other educational institutions in both higher education institutions and primary, secondary and upper education institutions to formal and non-formal educational institutions. This aims to dismantle the wall of scientific dichotomy which still shackles existing scientific developments. The concept of integration-interconnection is illustrated in the